Adaptation, now? : Exploring the Politics of Climate Adaptation through Poststructuralist Discourse Theory. - Remling, Elise; Gunnarsson Payne, Jenny; Persson, Åsa; Juhola, Sirkku (2019)
Increasing evidence of anthropogenic climate change and the recognition that warming is likely to go beyond 2°C raises the need for responses that help people cope with the anticipated changes.